Strategy for Sustainable Coastal Tourism Development in Sawang Indah Village, South Aceh Regency - Zulhamdi; Meutia, Zya Dyena; Aulia, Fahmi (Rumoh Journal of Architecture, 2023)
The coastal tourism area of Sawang Indah Village is one of the coastal tourist destinations located in Labuhanhaji Timur Subdistrict, South Aceh Regency. In its development, various issues have emerged related to the coastal tourism area. If left unaddressed, these problems may impact the sustainability and existence of the coastal tourism site.The objective of this study is to formulate a development strategy for the coastal tourism area in Sawang Indah Village, Labuhanhaji Timur Subdistrict, South Aceh Regency. This research employs a qualitative descriptive method to identify the characteristics of all aspects of tourism in the Sawang Indah coastal tourism area. Furthermore, a SWOT analysis is used to examine internal and external factors affecting all tourism aspects in the area. The combination of qualitative descriptive analysis and SWOT Matrix is then applied to formulate development strategies for the coastal tourism area in Sawang Indah Village. The results of this study present several strategic recommendations for the development of the coastal tourism area in Sawang Indah Village, including: 1. Conducting assessments to optimize existing and potential natural resources to create new natural attractions for tourists. 2. Planning the development of public facilities, including service improvement, renovation, spatial reorganization, maintenance, and facility expansion. 3. Designing attractive promotional content through online media platforms. 4. Planning road access expansion and road improvements. 5. Enhancing the role of the government and site managers through collaboration in policy-making and development planning. 6. Increasing local community involvement by establishing NGOs. 7. Developing the rest area as an information center as well as a hub for trade and services. 8. Improving the waste management system, including implementing written regulations and sanctions for tourists.